Family Intervention in Counseling Programs: A Quantitative Study of the Impact on Emotionally Disturbed Children - Rini Ambarwati; Marcus Tan; Isabelle Ng (Research Psychologie, Orientation et Conseil, 2025)
Emotionally disturbed children face significant challenges that affect their psychological well-being, academic performance, and social interactions. Traditional counseling programs often focus solely on the child, neglecting the crucial role of family dynamics in emotional development. Family intervention in counseling programs has emerged as a promising approach to addressing these issues by involving caregivers in the therapeutic process. This study aims to evaluate the impact of family-centered counseling programs on the emotional well-being of children diagnosed with emotional disturbances. A quantitative research design was employed, involving 120 children and their families, recruited from three counseling centers. Participants were randomly assigned to either a family intervention group or a standard counseling group. Data were collected over 12 weeks using validated instruments, including the Child Behavior Checklist (CBCL) and the Family Adaptability and Cohesion Evaluation Scale (FACES). Statistical analyses included paired t-tests and regression modeling to assess the effectiveness of the interventions. The results indicated that children in the family intervention group showed significant improvements in emotional regulation, reduced behavioral issues, and enhanced family cohesion compared to the standard counseling group. These findings highlight the importance of incorporating family dynamics into counseling programs to achieve better outcomes for emotionally disturbed children.